2015
DOI: 10.1063/1.4935890
|View full text |Cite
|
Sign up to set email alerts
|

Regimes of enhanced electromagnetic emission in beam-plasma interactions

Abstract: The ways to improve the efficiency of electromagnetic waves generation in laboratory experiments with high-current relativistic electron beams injected into a magnetized plasma are discussed. It is known that such a beam can lose, in a plasma, a significant part of its energy by exciting a high level of turbulence and heating plasma electrons. Beam-excited plasma oscillations may simultaneously participate in nonlinear processes resulting in a fundamental and second harmonic emissions. It is obvious, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…Recent PIC simulations with periodic boundary conditions [14,16] showed that, if the plasma thickness is comparable with the radiation wavelength, the power of electromagnetic emission near the frequency of the most unstable beam-driven mode can constitute the significant fraction (about 7%) of total beam power. It was also shown that the main features of observed radiation can be explained by the mechanism of plasma antenna.…”
Section: Generation Of Em Waves In Modulated Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent PIC simulations with periodic boundary conditions [14,16] showed that, if the plasma thickness is comparable with the radiation wavelength, the power of electromagnetic emission near the frequency of the most unstable beam-driven mode can constitute the significant fraction (about 7%) of total beam power. It was also shown that the main features of observed radiation can be explained by the mechanism of plasma antenna.…”
Section: Generation Of Em Waves In Modulated Plasmasmentioning
confidence: 99%
“…It has been experimentally found that reducing in plasma thickness down to the radiation wavelength is accompanied by the substantial increase in the radiation efficiency [13]. Recent PIC simulations [14] of the simplified temporal problem have shown that such a thin system with a longitudinal density modulation can radiate as a plasma antenna. Indeed, in a periodically perturbed plasma, the most unstable beam-driven wave generates superluminal satellites which are able to interact resonantly with the vacuum electromagnetic waves at the skin depth.…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally found that the beam power converts to radiation power much more efficiently when the typical transverse size of the beam-plasma system becomes comparable to the radiation wavelength [1]. These experiments have motivated theoretical studies on the mechanism of EM emission in the thin plasma case [2]. The feature of this regime is that a thin plasma column actually acts as an antenna which can efficiently radiate EM waves if a superluminal wave of electric current is excited inside the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The main pecularity of this regime is that a 100 keV electron beam creates a thin plasma column with the diameter comparable to the radiation wavelength [1]. Theoretical studies [2,3,4] motivated by these experiments have shown that such a high level of radiation efficiency can be explained by the mechanism of beam-plasma antenna. This theory is based on the fact that, in a thin plasma with a longitudinal density modulation, the beam-excited mode can generate the superluminal satellite which can resonate with vacuum electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%